A comparison of batch and semi-batch reactors for leaching battery cathodes (LiCoO2) under controlled addition of HCl and H2O2 - Cerrillo-González, María del Mar; Villén-Guzmán, María Dolores; Rivas-Bascon, Alvaro; Rodríguez-Maroto, José Miguel; Paz-García, Juan Manuel (Elsevier, 2024)
Recovery of cobalt and lithium from end-of-life Li-ion battery wastes have been evaluated in batch and semi- batch leaching systems. In this preliminary study, HCl and H2O2 were used as leaching and reducing agents, respectively. The comparison of batch and semi-batch processes was carried out, obtaining an improvement from 40% to 70% in the metal mass extracted (i.e. Co and Li) for semi-batch experiments under the same experimental conditions. Effects of the initial concentration of reducing and leaching agents were evaluated for a semi-batch system in which the acid was continuously fed to maintain a constant pH value. From experimental results, it was found that the concentration of H2O2 plays an important role in the leaching process in terms of selectivity. For the experiments carried out using 0.1 M of HCl and 1 M of H2O2, the percentage of Li and Co extracted was 90% for a leaching time of 30 min. The double-controlled addition of HCl and H2O2 to the semi-batch system allows the reduction of the H2O2 concentration to 0.5 M. The optimization of reactants entails not only the decrease of their consumption but also maximize the selectivity of the reactions desired, which represents promising results for the environmental sustainability of the process. Further work will examine the fate of chloride ions in the process.
Keywords: Lixiviación; Pilas de litio; Reciclado; Lithium-ion batteries; Recycling; Semi-batch reactor; Leaching